Variation of drought resistance of rice genotypes released in different years in China. (19th April 2019) - Wang, Baoxiang; Xu, Bo; Liu, Yan; Chen, Xubing; Liu, Jiawei; Zhi, Wenfang; Xing, Yungao; Yang, Bo; Li, Jian; Chi, Ming; Liu, Jinbo; Chen, Tingmu; et al.
Abstract: BACKGROUND: Drought is the most serious limiting factor of rice production worldwide and is becoming more intensive with climate change in recent years. Screening and breeding drought‐tolerant rice genotypes are essential to maintain yield gain and ensure food security under adverse environments. However, thus far, little attention has been given to the temporal changes of drought resistance concomitant with the year of release in rice genetic breeding. RESULTS: Sixteen rice genotypes bred or widely cultivated from 1934 to 2007 were grown in paddy fields (control) and upland fields (drought stress) to explore the variation of drought resistance in rice genotypes with the year of release. Grain yield and daily grain yield significantly increased with the year of release. The genetic improvements in the grain yield partially resulted from the significant increase in panicle, spikelets per panicle and filling percentage. In addition, various growth‐related characteristics like biomass, harvest index, relative growth rate, grain density and growth duration increased with an increase of genetic refinement of the genotypes through the years, and they contributed to improvement of final rice yields. However, grain yield, yield components and these growth‐related traits sharply declined under drought stress. Furthermore, the drought resistance coefficients of K Yield, K Daily grain yield, K Panicle number, K Spikelets per panicle, K Biomass, K Plant height, K Relative growth rate and K Filling percentage were prominently improved by genetic breeding. CONCLUSIONS: Drought resistance of rice genotypes has been significantly enhanced by genetic processes during the last 73 years in China, but they are still sensitive to drought conditions. Currently, there is still room for further improvement in drought resistance which is an important target in future breeding programs. © 2019 Society of Chemical Industry